IMPLEMENTASI MANAJEMEN PEMBELAJARAN MATEMATIKA DI KELAS VII A SMP INSAN CENDEKIA MANDIRI BOARDING SCHOOL SIDOARJO - Anida Rahmania; Muhammad Ripin Ikhwandi (ICO EDUSHA, 2022)
Implementation of Learning Management is defined as one of the components of success in education management. Learning Management arranges for learning to be realized properly. One of the supporters of the success that the Implementation of Learning Management is said to be successful is the implementation or good management. In this activity, the teacher plays a role in regulating how the management of learning in the classroom can run smoothly. Moreover, if the learning management applied in the classroom is in accordance with the characteristics of the students in the classroom. How well learning takes place, one of which depends on the teacher who applies the learning method. Learning in the field of mathematics is considered to be one of the lack of interest in learning it. This is because there is a lack of proper management in its application and makes mathematics a difficult and boring subject. The teacher's role in managing as a facilitator for students will produce different reactions if the learning method is applied properly. Therefore, on this basis, research was conducted at Insan Cendekia Mandiri Middle School in Sidoarjo regarding the Implementation of Class VII A Mathematics Learning Management to describe how the Implementation of Class VII A Mathematics Learning Management was carried out. In this study, the authors used descriptive qualitative methods in which field data were obtained from the results. interviews and observations. The results of the study indicate that the implementation of Mathematics Learning Management in class VII A of Insan Cendekia Mandiri Boarding School Sidoarjo Middle School in the POAC management function is carried out in learning, especially in the field of mathematics by the subject teacher. Keywords: Learning Management, Mathematics References adhar, Leo Effendi. (2012) “Pembelajaran Matematika Dengan Metode Penemuan Terbimbing Untuk Meningkatkan Kemampuan Representasi Dan Pemecahan Masalah Matematis Siswa Smp.” Jurnal Penelitian Pendidikan 13 No 2. http://jurnal.upi.edu/file/Leo_Adhar.pdf. Abdullah, Boedi. (2014) Manajemen Pendidikan Islam Bandung: CV Pustaka Setia. gunawan. (2020): “Penerapan Kerja Kelompok Kegiatan MGMP Guru Ekonomi Dalam Menyusun RPP Untuk Meningkatkan Kompetensi Pedagogik.” Celebes Publication Review 2, no. vol 2 no 1 33. Gunawan, Imam. (2019) Manajemen Kelas: Teori dan Aplikasinya, ed. 1. Depok: RajaGrafindo Pesada. Hidayati, (2020)Rahmatul Vivi, Nourma Wulandari Pramestie, Mohammad Maulyda Archi, Muhammad Erfan, and Awal Kholifatur Rosyidah Nur. “Literasi Matematika Calon Guru Sekolah Dasar Dalam Menyelesaikan Masalah PISA Konten Shape and Space.” Jurnal Pembelajaran Matematika Inovatif 3 no 3: 196. https://doi.org/10.22460/jpmi.v1i3. 185-194. Indarti, Luluk. (2020) Manajemen Pendidikan, Bogor: Guepedia. Isrok’atun dan Rosmala, (2015) Amelia, Model-model pembelajaran matrmatika Jakarta: Bumi Aksa. lado, hyronimus, gatot muhsetyo, and sisworo. (2016) “Penggunaan Media Bungkus Rokok Untuk Memahamkan Konsep Barisan Dan Deret Melalui Pendekatan RME,” no. 3 no 1: 1. misnih, and Aninda Galih. (2018) “peran guru dalam pengelolaan kelas.” jurnal profesi pendidikan dasar, no. Volume 5 No 1: 31. Nurulhaq, Dadan dan Supriastuti, Titin. (2020) Manajemen Pembelajaran Sejarah Kebudayaan Islam konsep strategi dalam meningkatkan akhlak peserta didik Bandung: CV Cendekia Press. prasetyo, Hendri. (2020) “Kemampuan Matematika Siwa Indonesia Berdasarkan TIMSS.” Jurnal Pedagogik Matematika 3, no. 2: 111. Pratama, Rheza. (2020) Pengantar Manajemen, Sleman: Deepublisher. Rasyid, Andi Pananrangi. (2017) Manajemen Pendidikan, Makassar: Celebes Media Perkasa. Rukajat, Ajat. (2018) Manajemen Pembelajaran Sleman: Deepublish. Rusman. (2012) model-model pembelajaran mengembangkan profesionalisme guru ed. Jakarta: PT Raja Grafindo Persada. Ruyatnasih, Yaya dan Megawati, Liya.(2017) Pengantar Manajemen, teori, fungsi dan kasus Yogyakarta: Absolute Media. Sutiah. (2016) teori belajar dan pembelajaran, Sidoarjo: Nizamia Learning Center Widiasworo, Erwin. (2017) Inovasi Pembelajaran Berbasis Lifeskill dan Enterpreneurship ed.1 Yogyakarta: Ar-Ruzz Media.